Chapter Introduction Critical Perspectives on Precarity and Precariousness - Choonara, Joseph (Bristol University Press, 2022)
The digital PDF of the Introduction of this title are available Open Access under CC-BY-NC-ND licence. The word 'precarity' is widely used when discussing work and employment, social conditions and lived experiences, and social classes. There is not, however, a consensus on the precise meaning of the term or how it should best be used to explore social changes. Bringing together an international group of thinkers from a diverse range of fields, this book offers a distinctive and critical perspective approach to an important topic.